Tinjauan Tentang Hukum Pidana Pemilu dan Formulasi Pertanggungjawaban dalam Tindak Pidana - Muridah Isnawati (Perspektif Hukum, 2018)
Accountability in the act of vote is inseparable from unsuccessful acts of election. Complications of problems that exist in elections, participation that does not involve parties involved in vote problems. Accountability for resolving vote actions must find the best formula in order to minimize the settlement that occurs in elections. Potential to avoid failure can occur before voting, during voting and after voting. The right formulation is needed as part of the anticipatory steps towards vote action. Collateral for anticipatory measures can be considered as part of a policy on crime prevention (criminal policy). In this case the formulation policy in the accountability of vote follow-up must be formulated coherently and integratively, with the basic principles needed in the administration of elections. For this reason, it is necessary to formulate accountability for election crimes that are eligible, effective and efficient, and transparent. This review of the formula for accountability for election can make the material for evaluating the policy formulation in the election follow-up.